2015
DOI: 10.1113/jp270423
|View full text |Cite
|
Sign up to set email alerts
|

Carotid body overactivity induces respiratory neurone channelopathy contributing to neurogenic hypertension

Abstract: Why sympathetic activity rises in neurogenic hypertension remains unknown. It has been postulated that changes in the electrical excitability of medullary pre-sympathetic neurones are the main causal mechanism for the development of sympathetic overactivity in experimental hypertension. Here we review recent data suggesting that enhanced sympathetic activity in neurogenic hypertension is, at least in part, dependent on alterations in the electrical excitability of medullary respiratory neurones and their centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 60 publications
2
19
0
Order By: Relevance
“…HCN channels are primarily permeable to K + ions, and, hence, their downregulation positively affects the excitability. This is consistent with the recent idea of peripheral chemoreceptor mediated channelopathy within the respiratory network in SHRs (Moraes et al, 2015). …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…HCN channels are primarily permeable to K + ions, and, hence, their downregulation positively affects the excitability. This is consistent with the recent idea of peripheral chemoreceptor mediated channelopathy within the respiratory network in SHRs (Moraes et al, 2015). …”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, SHR and CIH rat models of hypertension share many common features: 1) in both models, strengthened respiratory-sympathetic coupling are suggested to be involved in the development/maintenance of arterial hypertension (Zoccal et al, 2008, Moraes et al, 2014); 2) the carotid body chemoreceptors play a pivotal role for the development of hypertension in both models (Fletcher et al, 1992, Abdala et al, 2012); 3) the sympathetic response to peripheral chemoreceptors are amplified in SHR and CIH rats (Braga et al, 2006, Simms et al, 2009, Tan et al, 2010, Moraes et al, 2014), suggesting a sensitization of processing of peripheral chemoreceptor inputs; 4) SHR also exhibit a late-expiratory component in the AbN, in the cervical sympathetic and in the pre-sympathetic RVLM neuronal activity at normal (5%) CO 2 levels strongly resembling respiratory pattern of control (Wistar) animals at 7% CO 2 (Zoccal et al, 2008, Moraes et al, 2013, Moraes et al, 2014); and 5) SH animals also have a lower apneic threshold compared to Wistar rats (Moraes et al, 2014) similar to CIH vs. control (Molkov et al, 2011). Based on these similarities, we hypothesize that CIH-conditioned animals have altered baseline respiratory patterns due to increased excitability of pre-I/I population in pre-BötC because of the reduced leak conductance of these neurons (Moraes et al, 2014, 2015). We further test this hypothesis using computational modeling.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Moraes, Machado and co-workers (Moraes et al , 2013) reported that a specific population of non-catecholaminergic respiratory-modulated pre-sympathetic neurons in RVLM of IH exposed rats exhibit augmented excitatory synaptic inputs from the respiratory network. The enhanced excitatory synaptic activity of these neurons by IH was due to altered properties of the ion channels in post-inspiratory neurons (Moraes et al , 2015). Collectively, these studies indicate that altered neuronal coupling between the respiratory and pre-sympathetic neurons in the RVLM is an important central mechanism contributing to activation of the sympathetic nervous system by IH.…”
Section: Introductionmentioning
confidence: 99%